Synthesis of Tetra‐Substituted Trifluoromethyl‐3, 1‐Benzoxazines by Transition‐Metal‐Catalyzed Decarboxylative Cyclization of N‐Benzoyl Benzoxazinones. Issue 5 (19th February 2021) - Uno, Hiroto; Fujimoto, Daichi; Harada, Kyosuke; Tanaka, Chika; Shibata, Norio
Abstract: Efficient synthesis of N, O ‐heterocyclic tetra‐substituted trifluoromethyl‐3, 1‐benzoxazines via a transition‐metal‐catalyzed decarboxylative intramolecular cyclization was achieved. The decarboxylation of N ‐benzoyl trifluoromethyl‐benzoxazinones generated the amide oxygen nucleophile, allowing a selective internal C1 ‐attack on Pd‐ or Cu‐coordinated zwitterions, affording medicinally attractive tetra‐substituted vinyl‐ or ethynyl‐trifluoromethyl‐3, 1‐benzoxazines. This protocol can be applied to the synthesis of perfluoroalkyl‐ and non‐fluorinated 3, 1‐benzoxazines. Abstract : Efficient synthesis of N, O‐ heterocyclic tetra‐substituted trifluoromethyl‐3, 1‐benzoxazines via a transition‐metal‐catalyzed decarboxylative intramolecular cyclization was achieved. The decarboxylation of N‐benzoyl trifluoromethyl‐benzoxazinones generated the amide oxygen nucleophile, allowing a selective internal C1 ‐attack on Pd‐ or Cu‐coordinated zwitterions, affording medicinally attractive tetra‐substituted vinyl‐ or ethynyl‐trifluoromethyl‐3, 1‐benzoxazines. This protocol can be applied to the synthesis of perfluoroalkyl‐ and non‐fluorinated 3, 1‐benzoxazines.